Model-Based Control for Dual-Fuel Engines - Ichihashi, Hiroaki; Yamasaki, Yudai; Takashima, Yoshitane; Sako, Takahiro (Frontiers in Mechanical Engineering, 2020)
The dual-fuel engine (DFE) has been focused on in order to improve its efficient use of natural gas. It has been reported that in DFE the combustion efficiency of the natural gas decreases at a low load. In an attempt to tackle this problem, it has been reported that a multi-stage diesel injection can improve the combustion efficiency of natural gas at a low load. The aim of this research is, therefore, to explain the mechanism for improving combustion efficiency with a multi-stage diesel injection and to develop a control model that predicts engines' combustion efficiency by multi-stage injection. Additionally, a controller was developed using the control model to improve the combustion efficiency by changing the diesel injection conditions. Experimental results show that the controller improves combustion efficiency. Furthermore, taking in to account the heat ratio of natural gas to diesel fuel in addition to combustion efficiency, it has been shown that it is possible to design a controller to leverage the advantage of DFE, which reduces the quantity of fossil fuels.